IMPLEMENTATION OF VERSION 1.0 SIMKIM TO SIMKIM VERSION 2.0 ON THE ISSUANCE OF CASE STUDY PASSPORT IMMIGRATION OFFICE OF NON-BORDER CONTROL SOUTH JAKARTA - Salma Nabila Rianissa (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
The application of immigration information technology at the Immigration Checkpoint (TPI) is a very important matter to always be considered and developed in the very long term in the future, one of them is to focus on developing the autogate system. With some literacy regarding immigration information technology at TPI in several countries, it can result in several comparisons between the immigration information technology system in Indonesia with the immigration information technology system in several foreign countries. This can be used as study or learning material in seeing some of the shortcomings or gaps that the immigration technology information system in Indonesia has. The results of the study carried out with this qualitative research method have explained that the immigration information technology system in TPI Indonesia still has several gaps or shortcomings when compared to the existing systems in several other countries. So, it is very necessary to make several further studies or research related to the development of an immigration information technology system at TPI Indonesia that can adapt several existing systems in several countries.